2013
DOI: 10.1136/jclinpath-2013-201870
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated Akt expression is a prognostic marker in early-stage non-small cell lung cancer

Abstract: Level of expression of pAkt in the cytoplasm and nucleus is an independent prognostic factor that may help to select patients with high-risk disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…(27) Recently, it was described that cases expressing nuclear p-Akt showed a poorer prognosis. (28) Nonetheless, other investigators have suggested that cancers expressing p-Akt in the nucleus have a better prognosis and responded better to targeted therapy. (19) Analytical methods have recently been further refined due to the development of commercially available isoform-specific or phosphorylated-form-specific antibodies applicable to IHC on paraffin-embedded tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(27) Recently, it was described that cases expressing nuclear p-Akt showed a poorer prognosis. (28) Nonetheless, other investigators have suggested that cancers expressing p-Akt in the nucleus have a better prognosis and responded better to targeted therapy. (19) Analytical methods have recently been further refined due to the development of commercially available isoform-specific or phosphorylated-form-specific antibodies applicable to IHC on paraffin-embedded tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found that expression of p‐Akt was not associated with prognosis, and was even associated with longer survival, but other studies showed a poorer prognosis . Recently, it was described that cases expressing nuclear p‐Akt showed a poorer prognosis . Nonetheless, other investigators have suggested that cancers expressing p‐Akt in the nucleus have a better prognosis and responded better to targeted therapy .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in renal cell carcinoma, Pantuck et al found that high nuclear p-AKT expression was associated with a favorable prognosis, while high cytoplasmic p-AKT expression was associated with a poor prognosis [92]. Conversely, a study in patients with non-small cell lung cancer observed that higher levels of cytoplasmic p-AKT had a trend toward longer overall survival; whereas higher levels of nuclear p-AKT had a poorer prognosis [93]. In general, investigators have identified an association between ERK activation and poor prognosis such as aggressive neoplastic features, metastasis, and reduced survival [94,95].…”
Section: Leptin Biology and Molecules Of Relevant Signal Transductmentioning
confidence: 99%
“…Several clinical studies have revealed that lymphatic invasion is more frequently observed in cancers with higher leptin expression in different tumor types. [9][10][11] There is growing evidence that leptin enhances invasion and metastasis in breast, ovarian, lung, gallbladder, and pancreatic cancers, etc. [12][13][14][15][16] In our previous study, we demonstrated that leptin is upregulated in migration-prone cell lines, and exogenous leptin also enhances the migration ability of glioma cells.…”
Section: Introductionmentioning
confidence: 99%